2014
DOI: 10.15288/jsad.2014.75.945
|View full text |Cite
|
Sign up to set email alerts
|

Do Positive Alcohol Expectancies Have a Critical Developmental Period in Pre-Adolescents?

Abstract: ABSTRACT. Objective: Positive outcome expectancies have been shown to predict initiation of alcohol use in children and to mediate and moderate the relationship between dispositional variables and drinking behavior. Negative outcome expectancies for alcohol appear to weaken as children progress to middle adolescence, but positive expectancies tend to increase during this time. Positive alcohol expectancies have been found to increase in children in third and fourth grades, indicating what some investigators ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
0
24
0
3
Order By: Relevance
“…The current study examined the effect of parental smoking on children’s implicit and explicit responses towards smoking behavior and smoking-related cues with the goal of identifying potential cognitive mechanisms to explain the relationship between parental smoking and child smoking perceptions. We chose to focus on the responses of children between the ages of 8–12 years (hereafter referred to as pre-adolescents) in the current study because this group is particularly vulnerable to smoking initiation (Baker, Brandon, & Chassin, 2004; Copeland, Proctor, Terlecki, Kulesza, & Williamson, 2014). One reason for this is that pre-adolescents’ health-related beliefs are more malleable than those of adolescents (Eagly & Chaiken, 1993).…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The current study examined the effect of parental smoking on children’s implicit and explicit responses towards smoking behavior and smoking-related cues with the goal of identifying potential cognitive mechanisms to explain the relationship between parental smoking and child smoking perceptions. We chose to focus on the responses of children between the ages of 8–12 years (hereafter referred to as pre-adolescents) in the current study because this group is particularly vulnerable to smoking initiation (Baker, Brandon, & Chassin, 2004; Copeland, Proctor, Terlecki, Kulesza, & Williamson, 2014). One reason for this is that pre-adolescents’ health-related beliefs are more malleable than those of adolescents (Eagly & Chaiken, 1993).…”
Section: The Current Studymentioning
confidence: 99%
“…One reason for this is that pre-adolescents’ health-related beliefs are more malleable than those of adolescents (Eagly & Chaiken, 1993). Additionally, pre-adolescence is a key period for increasing positive outcome expectancies and decreasing negative outcome expectancies (Copeland et al, 2014), which may be important as previous work demonstrated that children’s perceptions of smoking become more positive as they near adolescence (Pisano & Rooney, 1988). Finally, research suggests that experimentation with cigarettes typically begins to occur after 12 years of age (Bauman & Phongsavan, 1999; Mowery, Farrelly, Haviland, Gable, & Wells, 2004; Winkleby, Fortmann, & Rockhill, 1993), making pre-adolescence a critical time period to examine beliefs about smoking and responses to smoking cues.…”
Section: The Current Studymentioning
confidence: 99%
“…a feeling of euphoria and achievement, and due to positive expectancies. 22 However, frequently, in other larger subpopulations of alcohol-dependent patients, and most often in later stages of the addiction, once it has completely developed, drinking becomes a compulsive process. 23 It means that drinking is essentially a way to escape negative affects and feelings.…”
Section: A Role For Dysbiosis In the Negative Reinforcement Processmentioning
confidence: 99%
“…Furthermore, several factors that might shape a person’s endorsement of alcohol expectancies, particularly in young population, have been examined. Positive alcohol expectancies were found to increase and negative alcohol expectancies generally decline during adolescence when the risk of alcohol initiation and problematic drinking escalates [3436]. Other than developmental stage or age, predictors of alcohol expectancies included an array of individual characteristics (e.g., gender, pubertal development, genetics) and environmental factors (e.g., parental drinking, peer drinking, peer network, and alcohol advertisement) [3541].…”
Section: Introductionmentioning
confidence: 99%